Use of health services and medication use, new comorbidities, and mortality in patients with chronic diseases who did not contract COVID-19 during the first year of the pandemic: a retrospective study and comparison by sex - Liliana Mahuela; Bárbara Oliván-Blázquez; Ana Lear-Claveras; Fátima Méndez-López; Mario Samper-Pardo; Sandra León-Herrera; Rosa Magallón-Botaya; María Antonia Sánchez-Calavera (BMC, 2023)
Abstract Background The restrictions introduced to stop the spread of the COVID-19 virus have also had a direct impact on people with chronic diseases and especially on diseases to which lifestyles are relevant in their control and management, such as diabetes, hypertension, chronic obstructive pulmonary disease (COPD), etc. The purpose of this paper is to conduct a longitudinal analysis of new comorbidities, mortality, medication use, and the use of health resources in patients with chronic diseases who did not contract COVID-19, comparing the six months before the strict lockdown to the 12 months following the end of the strict lockdown. Method An observational real world data pre-post study of 668,974 people was undertaken. The patients studied were over 16 years of age, had been receiving care from the Aragon Health Service (Northeastern Spain), were diagnosed with one or more chronic diseases, and had not contracted COVID-19. Sociodemographic, comorbidity, pharmacological and health resource use variables were collected during the six months before the onset of the lockdown and during the six and 12 months following the end of the lockdown. The comparisons by sex were carried out using a Student T-test or chi-squared test to analyse differences. Results Dyslipidaemia (42.1%) followed by hypertension (35.1%) and anxiety and depression (34.6%) were the most prevalent chronic diseases among the study population. 78.% of patients had between one and four chronic illnesses. There was a decrease in new diagnoses of other chronic comorbidities in this population and a decrease in medications prescribed and the use of health services.  Although women received more diagnoses of chronic diseases, the number of medications dispensed was lower, but the use of health services was higher. These figures were maintained throughout the pandemic. Conclusion Our results suggest an underdiagnosis of new chronic comorbidities and a decrease in mortality rates from causes unrelated to COVID-19 due to the closure of health centres in Aragón (Spain) during the lockdown. This trend was exacerbated in women. The underdiagnosis of new chronic comorbidities during confinement can cause the disease to worsen, with the consequent increase in symptoms and the worsening of chronic pathologies in patients with a severe evolution.